Expression of the Autoimmune Regulator Gene and Its Relevance to the Mechanisms of Central and Peripheral Tolerance. (22nd October 2012) - Perniola, Roberto
Abstract : The autoimmune polyendocrine syndrome type 1 (APS-1) is a monogenic disease due to pathogenic variants occurring in the autoimmune regulator ( AIRE ) gene. Its related protein, AIRE, activates the transcription of genes encoding for tissue-specific antigens (TsAgs) in a subset of medullary thymic epithelial cells: the presentation of TsAgs to the maturating thymocytes induces the apoptosis of the autoreactive clones and constitutes the main form of central tolerance. Dysregulation of thymic AIRE expression in genetically transmitted and acquired diseases other than APS-1 may contribute to further forms of autoimmunity. As AIRE and its murine homolog are also expressed in the secondary lymphoid organs, the extent and relevance of AIRE participation in the mechanisms of peripheral tolerance need to be thoroughly defined.